2008
DOI: 10.1186/1471-2180-8-145
|View full text |Cite
|
Sign up to set email alerts
|

A novel receptor – ligand pathway for entry of Francisella tularensis in monocyte-like THP-1 cells: interaction between surface nucleolin and bacterial elongation factor Tu

Abstract: Background: Francisella tularensis, the causative agent of tularemia, is one of the most infectious human bacterial pathogens. It is phagocytosed by immune cells, such as monocytes and macrophages. The precise mechanisms that initiate bacterial uptake have not yet been elucidated. Participation of C3, CR3, class A scavenger receptors and mannose receptor in bacterial uptake have been already reported. However, contribution of an additional, as-yetunidentified receptor for F. tularensis internalization has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 53 publications
(86 reference statements)
2
80
0
Order By: Relevance
“…Several recovered proteins are predicted to be cytoplasmic. While many of these socalled cytoplasmic proteins were recovered in another surface biotinylation and affinity proteomic study of A. phagocytophilum or have homologs in other bacteria that localize to and function on bacterial surfaces (47,(55)(56)(57)(58)(59)(60)(61)(62)(63)(64), it remains to be verified if all recovered proteins in this study are in fact surface localized. Though we initially identified Asp14 on the A. phagocytophilum DC surface, indirect immunofluorescence analyses revealed that the bacterium constitutively expresses Asp14 throughout its development in HL-60, RF/6A, and ISE6 cells.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Several recovered proteins are predicted to be cytoplasmic. While many of these socalled cytoplasmic proteins were recovered in another surface biotinylation and affinity proteomic study of A. phagocytophilum or have homologs in other bacteria that localize to and function on bacterial surfaces (47,(55)(56)(57)(58)(59)(60)(61)(62)(63)(64), it remains to be verified if all recovered proteins in this study are in fact surface localized. Though we initially identified Asp14 on the A. phagocytophilum DC surface, indirect immunofluorescence analyses revealed that the bacterium constitutively expresses Asp14 throughout its development in HL-60, RF/6A, and ISE6 cells.…”
Section: Discussionmentioning
confidence: 85%
“…APH_0240 (the chaperonin GroEL), APH_0346 (DnaK), and APH_1032 (the elongation factor Tu) were chosen because these housekeeping proteins have been shown to moonlight as surface proteins in A. phagocytophilum and other bacteria. Moreover, these proteins have been implicated as adhesins in other bacteria (47,(55)(56)(57)(58)(59)(60)(61)(62)(63)(64). Of the 11 candidates, Omp-1A, Omp85, Msp5, and APH_0441 carry predicted N-terminal signal peptide sequences.…”
Section: Resultsmentioning
confidence: 99%
“…The scavenger A receptor (SRA), although traditionally known to play a role in uptake of unopsonized bacteria, contributes to the uptake of serum-opsonized Francisella, since SRA Ϫ/Ϫ macrophages exhibit a 20% reduction in the uptake of serumopsonized LVS (176). Macrophage cell surface-exposed nucleolin has also been implicated in uptake of serum-opsonized Francisella by binding the bacterial membrane protein EF-Tu (19). Finally, MR-mediated uptake also plays a role in uptake of serum-opsonized Francisella (roughly 30% decreased uptake when blocked) (90).…”
Section: Mechanisms Of Entry and Fate Of Intracellular Francisellamentioning
confidence: 99%
“…For this reason, many studies have focused on elucidating the Francisella life cycle in this cell type. Receptors that mediate phagocytosis of opsonized and unopsonized bacteria have been described and include complement receptor 3 (CR3) (CD11b/CD18), complement receptor 4 (CR4) (CD11c/ CD18), scavenger receptor A, mannose receptor, and nucleolin (5)(6)(7)(8)(9)(10). Shortly after uptake, both F. tularensis and F. novicida disrupt phagosome maturation so that phagosome-lysosome fusion is impaired and bacteria escape from a late-endosome-like compartment to replicate in the macrophage cytosol (11)(12)(13)(14).…”
mentioning
confidence: 99%